2000
DOI: 10.1128/iai.68.10.5846-5855.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Postgenomic Approach to Identification ofMycobacterium leprae-Specific Peptides as T-Cell Reagents

Abstract: To identify Mycobacterium leprae-specific human T-cell epitopes, which could be used to distinguish exposure to M. leprae from exposure to Mycobacterium tuberculosis or to environmental mycobacteria or from immune responses following Mycobacterium bovis BCG vaccination, 15-mer synthetic peptides were synthesized based on data from the M. leprae genome, each peptide containing three or more predicted HLA-DR binding motifs. Eighty-one peptides from 33 genes were tested for their ability to induce T-cell response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…In the present study, instead of abandoning the nonspecific molecules as diagnostic reagents, we dissected the proteins by testing overlapping peptides spanning their sequence and divided them into specific and nonspecific moieties. A peptide-based diagnostic approach has also been attempted for leprosy, but although high specificity was demonstrated, the selected specific peptides gave a relatively low sensitivity (14). We made the same observation in the present study; selecting only the regions of the protein without cross-reactive epitopes decreased the sensitivity.…”
Section: Discussionsupporting
confidence: 70%
“…In the present study, instead of abandoning the nonspecific molecules as diagnostic reagents, we dissected the proteins by testing overlapping peptides spanning their sequence and divided them into specific and nonspecific moieties. A peptide-based diagnostic approach has also been attempted for leprosy, but although high specificity was demonstrated, the selected specific peptides gave a relatively low sensitivity (14). We made the same observation in the present study; selecting only the regions of the protein without cross-reactive epitopes decreased the sensitivity.…”
Section: Discussionsupporting
confidence: 70%
“…Scrutiny of the M. leprae genome revealed the presence of two candidate genes, ML0049 and ML0050, that encode the M. leprae homologs of ESAT-6 and CFP-10, respectively (16,17,21,22). We recently reported that recombinant M. leprae ESAT-6 and CFP-10 proteins were efficiently recognized by T cells from the majority of M. leprae responsive leprosy patients (12,16). Despite limited sequence identity with their M. tuberculosis homologues Rv3875 and Rv3874 (36 and 40%, respectively), however, significant immunologic cross-reactivity with M. tuberculosis proteins was found for human T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the completion of the M. leprae genome sequence, the search for M. leprae-specific antigens that stimulate cellular rather than humoral immunity led to the identification of several antigens and peptides that were able to induce T-cell responses in vitro (12,16,17). Unfortunately, for most of these antigens, homologues were later found in other mycobacteria, including M. tuberculosis, which limits the diagnostic potential of these antigens for leprosy (6,21,22).…”
mentioning
confidence: 99%
“…A previous study using M. leprae-derived peptides showed considerable variation in peptide reactivity at different sites (8). Thus, in order to estimate the potential of the peptides for detecting M. lepraespecific T-cell immunity in the context of genetically different backgrounds, we selected the most promising peptides (n ϭ 22) and proteins (n ϭ 5) from the previous studies in Brazil, four other countries of leprosy endemicity in Asia (Nepal, Bangladesh, and Pakistan) and Africa (Ethiopia), and an additional site in west central Brazil (Goiás State).…”
Section: The Detection Of Hundreds Of Thousands Of New Cases Of Lepromentioning
confidence: 99%